2010
DOI: 10.4103/0970-9290.66631
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral lower second molar impaction in teenagers: An emergent problem?

Abstract: The frequency of simultaneously impacted second and third molars in teenagers is increasing and becoming a common occurrence in adolescent oral surgery practice. The traditional treatment is the removal of the third molar by conventional access but repositioning of the surgical flap to the distal face of the first molar can predispose to complications such as pericoronitis and delayed healing of the attached gingiva. We present a case in which we use the germectomy approach to remove the impacted third molar f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…As regards the Plaque Indexes, as a matter of fact, no statistically significant differences have been shown during the different study checks (preoperatorial, 10 th , 17 th /20 th and 90 th day) (6, 7). The periodontal recovery has been shown by the probing values, which were on the average better than the starting ones (8). Figure 5 shows the loss of attachment of the sites around the second lower molar.…”
Section: Discussionmentioning
confidence: 99%
“…As regards the Plaque Indexes, as a matter of fact, no statistically significant differences have been shown during the different study checks (preoperatorial, 10 th , 17 th /20 th and 90 th day) (6, 7). The periodontal recovery has been shown by the probing values, which were on the average better than the starting ones (8). Figure 5 shows the loss of attachment of the sites around the second lower molar.…”
Section: Discussionmentioning
confidence: 99%
“…Bjornland et al have observed complications in 1.8% of cases in their study. From a surgical point of view, enucleations of the wisdom teeth would be relatively uncomplicated procedures, but the enucleations of the maxillary M3 are technically more difficult to do 26 . The question arises as to whether the premature removal of the M3 deprives the retromolar region of a significant potential for growth.…”
Section: Early Removal Of the Wisdom Teethmentioning
confidence: 99%
“…Studies show that with environmental modifications, the dento-maxillary discrepancies (DMD) tend to increase 8 . But some authors are beginning to see a relationship between an increase in impactions of the second molars with the reduction in the rate of extractions of premolars in modern therapeutics 1,12,16,23,26,27 .…”
Section: Introductionmentioning
confidence: 99%